LAYANAN JAGA KESEHATAN MENTAL DAN EMOSI REMAJA DI KALIMANTAN SELATAN - Dina Lutfia Anggraeni; Dahliani Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The increasing number of mental and emotional disorders among adolescents in South Kalimantan, particularly in Banjarbaru City, highlights the urgent need for a preventive platform to help young people maintain their mental and emotional well-being. The lack of youth-friendly mental health facilities and the persistent negative stigma surrounding mental illness are the main challenges. This study aims to design a mental health service based on the Healing Environment approach, which seeks to create a preventive environment. The design method used in this project employs the Healing Environment approach, in which design elements applied to the building and site include natural lighting, cross ventilation, calming color schemes, integration of green open spaces, and the provision of various facilities such as hypnotherapy rooms, art spaces, expression rooms, and spiritual activity areas. The design outcomes show that a consciously and naturally designed physical environment can have a positive impact on the psychological state of adolescents. In this context, architecture does not only serve as a container for activities but also as a medium for healing and prevention of mental health issues before they become more serious. Through the integration of various functional spaces such as hypnotherapy rooms, “Our Story” rooms, painting rooms, writing rooms, music studios, and educational spaces like seminar halls and discussion areas with spiritual dimensions, the design supports healthy emotional expression and social interaction. The inclusion of natural elements such as natural lighting, cross ventilation, green visuals, and open spaces enhances a calming and soul-refreshing atmosphere.